Inhibition of fibroblast activation protein and dipeptidylpeptidase 4 increases cartilage invasion by rheumatoid arthritis synovial fibroblasts - Ospelt, Caroline; Mertens, Joachim C.; Jüngel, Astrid; Brentano, Fabia; Maciejewska-Rodriguez, Hanna; Huber, Lars C.; Hemmatazad, Hossein; Wüest, Thomas; Knuth, Alexander; Gay, Renate E.; Michel, Beat A.; Gay, Steffen; et al. (Arthritis & rheumatism, 2010)
Objective Since fibroblasts in the synovium of patients with rheumatoid arthritis (RA) express the serine proteases fibroblast activation protein (FAP) and dipeptidylpeptidase 4 (DPP-4)/CD26, we undertook the current study to determine the functional role of both enzymes in the invasion of RA synovial fibroblasts (RASFs) into articular cartilage. Methods Expression of FAP and DPP-4/CD26 by RASFs was analyzed using fluorescence-activated cell sorting and immunocytochemistry. Serine protease activity was measured by cleavage of fluorogenic substrates and inhibited upon treatment with L-glutamyl L-boroproline. The induction and expression of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in RASFs were detected using real-time polymerase chain reaction. Densitometric measurements of MMPs using immunoblotting confirmed our findings on the messenger RNA level. Stromal cell-derived factor 1 (SDF-1 [CXCL12]), MMP-1, and MMP-3 protein levels were measured using enzyme-linked immunosorbent assay. The impact of FAP and DPP-4/CD26 inhibition on the invasiveness of RASFs was analyzed in the SCID mouse coimplantation model of RA using immunohistochemistry. Results Inhibition of serine protease activity of FAP and DPP-4/CD26 in vitro led to increased levels of SDF-1 in concert with MMP-1 and MMP-3, which are downstream effectors of SDF-1 signaling. Using the SCID mouse coimplantation model, inhibition of enzymatic activity in vivo significantly promoted invasion of xenotransplanted RASFs into cotransplanted human cartilage. Zones of cartilage resorption were infiltrated by FAP-expressing RASFs and marked by a significantly higher accumulation of MMP-1 and MMP-3, when compared with controls. Conclusion Our results indicate a central role for the serine protease activity of FAP and DPP-4/CD26 in protecting articular cartilage against invasion by synovial fibroblasts in RA.